The Functions Of Metaphorical Terms Linked With “Health” - Yuldasheva Dilfuza Shonazar qizi (Peerian Journals Publishing, 2024)
This thesis is related to the importance of functions and semantics of the metaphors. The impact of metaphors on different illnesses, like cancer, offer a relevant study for our purposes, because there is a proof that metaphors may play a major and potentially beneficial role in the relationship of people with the diseases. Moreover, three dominant concepts (patient, disease and physician), which are related to the concept “health” were explained by means of metaphorical terms, based on the aspects of war metaphors, parental metaphors, engineering metaphors and sport metaphors.
Keywords: concept; speech; term; phrase